PRENATAL INVESTIGATION AND MANAGEMENT OF NON-IMMUNE HYDROPS FETALIS - A, Pulatova G; B, Yusupbaev R (Journal of Medical Genetics and Clinical Biology, 2024)
Background: Advances in medicine have significantly improved our ability to address various diseases affecting the unborn child, with fetal medicine emerging as a rapidly evolving field. Specific Background: Nonimmune hydrops fetalis, a severe antenatal pathology requiring advanced minimally invasive treatment techniques, exemplifies the critical challenges and progress in fetal medicine. Knowledge Gap: Despite advancements, there remains a need for a comprehensive review of nonimmune hydrops fetalis, encompassing its etiology, clinical presentation, and management, particularly with regard to recent data from specialized fetal medicine departments. Aims: This article aims to review the multifaceted aspects of nonimmune hydrops fetalis, including its causes, diagnostic approaches, and treatment options, while providing insights from recent cases managed within a fetal medicine department. Results: The review covers the etiology of nonimmune hydrops fetalis, which can be attributed to a range of genetic, cardiac, and infectious factors. It discusses the clinical presentation and highlights advancements in antenatal diagnosis and management. Additionally, the article presents case studies from the fetal medicine department, illustrating contemporary approaches and outcomes. Novelty: This review provides an updated synthesis of nonimmune hydrops fetalis management and diagnosis, integrating recent case studies and technological advancements. Implications: The findings underscore the importance of continued research and innovation in fetal medicine to enhance the diagnosis and management of nonimmune hydrops fetalis, ultimately improving outcomes for affected pregnancies.